Effect of packaging methods on salt-reduced smoked-steamed ham using herbal extracts - Adrian Stelmasiak; Jarosław Wyrwisz; Agnieszka Wierzbicka (CyTA - Journal of Food, 2019)
The aim of the study was to analyze the using of herbal extracts on reduced-salt smoked-steamed ham and to choose the optimal method of packaging. The 36 muscles were allocated to three groups: standard (S) with a content of NaCl = 2.5% and two experimental groups. The first one with a reduced salt content to 1.5% by the using of basil extract (E1) and the second group with an addition of oregano (E2). Hams were storage for 10, 20 and 30 days after packaging in barrier bags, vacuum conditions and modified atmosphere condition. The results indicate that the addition of herbal extracts increases the polycyclic aromatic hydrocarbons content (P < 0.05) but does not cause exceeded the recommended standards. The most advantageous packaging technology for hams with reduced salt content is vacuum. These hams were characterized by the most advantageous color parameters and the lowest hardness.